1996
DOI: 10.1063/1.116455
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer scale conductance change in a Langmuir-Blodgett film with the atomic force microscope

Abstract: A nanometer scale metal/Langmuir-Blodgett (LB) film/metal structure is realized with an atomic force microscope combined with scanning tunneling microscope (AFM/STM). Even in this nanometer scale configuration, increase in conductance can be induced at any point in the LB film by application of a voltage pulse. The AFM/STM observation shows little surface modification has occurred by the voltage application, which shows that the conductance of the LB film changes without pit formation in the LB film or metal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Various materials have been used for preparing thin films as storage media, such as photoconductor material, 3 Ge 2 Sb 2 Te 4 , 4 ␤-Na x V 2 O 5 , 2-5 polyimide Langmuir-Blodgett film, 7 and organic-complex material. 8 In our earlier study, two kinds of organic material were used for preparing organic complex thin films.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Various materials have been used for preparing thin films as storage media, such as photoconductor material, 3 Ge 2 Sb 2 Te 4 , 4 ␤-Na x V 2 O 5 , 2-5 polyimide Langmuir-Blodgett film, 7 and organic-complex material. 8 In our earlier study, two kinds of organic material were used for preparing organic complex thin films.…”
mentioning
confidence: 99%
“…Sakai and coworkers [7,8] showed that memory switching between a high-impedance state (OFF state) and a high-conductance state (ON state) occurs reproducibly in the metal/polyimide (PI) or squarylium dye (SQ) LB films/metal device with a noble-metal base electrode. Yano et al [9]. showed that a nanometer-scale metal/ PI LB films/metal structure was realized as determined using atomic force microscopy (AFM)/scanning tunneling microscopy (STM), and that the conductance of the PI LB films changed on a nanometer scale with no pit formation or metal cluster deposition from the tip of the probe.…”
Section: Introductionmentioning
confidence: 99%
“…This ability makes the SPMs powerful tools for developing ultrahigh density data storage devices. Various materials as storage media have been investigated, for example, ␤-Na x V 2 O 5 , 1,2 GeSb 2 Te 4 , 3 PI LB film, 4 Ag-TDCN ͑Ref. 5͒ film, etc.…”
Section: Introductionmentioning
confidence: 99%